Addendum Guidelines for the Prevention of Peanut Allergy in the United States: Report of the National Institute of Allergy and Infectious Diseases–Sponsored Expert Panel. Issue 1 (January 2017) - Togias, Alkis; Cooper, Susan F.; Acebal, Maria L.; Assa'ad, Amal; Baker, James R.; Beck, Lisa A.; Block, Julie; Byrd‐Bredbenner, Carol; Chan, Edmond S.; Eichenfield, Lawrence F.; Fleischer, David M.; Fuchs, George J.; et al.
Abstract: Background: Food allergy is an important public health problem because it affects children and adults, can be severe and even life‐threatening, and may be increasing in prevalence. Beginning in 2008, the National Institute of Allergy and Infectious Diseases, working with other organizations and advocacy groups, led the development of the first clinical guidelines for the diagnosis and management of food allergy. A recent landmark clinical trial and other emerging data suggest that peanut allergy can be prevented through introduction of peanut‐containing foods beginning in infancy. Objectives: Prompted by these findings, along with 25 professional organizations, federal agencies, and patient advocacy groups, the National Institute of Allergy and Infectious Diseases facilitated development of addendum guidelines to specifically address the prevention of peanut allergy. Results: The addendum provides three separate guidelines for infants at various risk levels for the development of peanut allergy and is intended for use by a wide variety of health care providers. Topics addressed include the definition of risk categories, appropriate use of testing (specific IgE measurement, skin prick tests, and oral food challenges), and the timing and approaches for introduction of peanut‐containing foods in the health care provider's office or at home. The addendum guidelines provide the background, rationale, and strength of evidence for each recommendation. Conclusions: Guidelines have been developed for early introduction of peanut‐containing foods into the diets of infants at various risk levels for peanut allergy.